The Origins of Polish Rhythms - Dahlig-Turek, Ewa (ACADEMIA. The magazine of the Polish Academy of Sciences, 2004)
According to music sources, the origins of the Polish national dances - the mazurka and polonaise - can be traced back to the 16th century. German composers and theorists of that period were first to notice special Polish rhythms that soon became popular in European music.